Loss-resistant bamboo mould-proof modification method
Through the modification of multiple acid emulsification and polymerization diversion in bamboo materials, the anti -mildew layer of the in situ aggregation and esterization reactions is formed, which solves the problem of preventing mold prevention in the existing technology. The long -term effect and texture protection of bamboo materials.
Patent Information
- Application Number
- CN202411548275.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-24
AI Technical Summary
The existing bamboo anti-mold modification technology has the problem of water-soluble loss of modifiers, resulting in anti-mold failure, making it difficult to achieve long-term anti-mold effect.
The multi -acid emulsion methacryal acrylic hydroglceride is made of micro -emulsion, and a polymerous diversion agent is added to form a modified solution. By impregnating and thermal treatment, the modified agent occurs in original polymerization and esterization reactions inside the bamboo material to form anti -loss prevention of loss of loss. Mold bamboo.
The complete anti-mildew effect of bamboo has been achieved. When the solute concentration of the modified reagent reaches more than 8 wt%, it can maintain complete anti-mildew performance after being immersed in water for 5 days without releasing irritating gases and maintaining the original color and texture of bamboo.
Smart Images

Figure CN119347908A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bamboo modification, and in particular relates to a method for anti-loss and anti-mildew modification of bamboo. Background Art
[0002] Bamboo has the advantages of fast growth, high yield, good toughness and easy processing. In recent years, it has been widely used in the fields of construction, papermaking, textiles, furniture, etc. However, bamboo contains a large amount of nutrients, which provide the nutrients needed for the growth and reproduction of mold, resulting in the bamboo being very easy to mold during storage, transportation and use. Mold not only affects the use value and economic value of bamboo and its products, but also poses a threat to human health. Therefore, it is necessary to carry out mildew-proof treatment on bamboo, improve the mildew-proof efficiency of bamboo, and promote the efficient processing and utilization of bamboo, which is of great significance to the industrialization development of bamboo.
[0003] CN109366653A discloses a long-term mildew-proof and wear-resistant processing method for bamboo, which adopts a physical ball milling method to uniformly mix SiO2@Ag nanoparticles with a core-shell structure and oil in a mass fraction ratio of 5 to 10:100, and vacuum impregnation is used to allow the modified SiO2@Ag nanoparticles to enter the interior of the bamboo to obtain mildew-proof bamboo.
[0004] CN107443518A discloses a processing method for low-temperature oil-heat-modified bamboo, which comprises immersing the bamboo in hot oil with a coupling agent added thereto, cooling and drying the bamboo, and then carbonizing and sealing the cross section thereof.
[0005] CN114670301A discloses a bamboo material with mildew resistance and a modification method thereof. 6-15% acrylamide derivative monomer and a catalyst are uniformly mixed to prepare a modified solution, and the acrylamide derivative monomer is allowed to enter the interior of the bamboo material by vacuum pressure impregnation. After in-situ polymerization, the bamboo material with good mildew resistance is obtained.
[0006] The above-mentioned bamboo anti-mildew modification technologies all have the problem of water-soluble loss of the modifier, resulting in anti-mildew failure. At present, bamboo treated with anti-mildew agents also has the problem of difficulty in long-term anti-mildew due to water-soluble loss of the anti-mildew agent. Summary of the invention
[0007] The object of the present invention is to overcome at least one disadvantage of the prior art and provide a method for improving the mildew resistance of bamboo materials.
[0008] The technical solution adopted by the present invention is: In a first aspect, the present invention provides a method for improving the anti-mildew property of bamboo materials, the method comprising the following steps: 1) Emulsifying glycidyl methacrylate with polyacid to prepare microemulsion; 2) adding a polymerization initiator to the microemulsion obtained in step 1) to obtain a modified solution, and then impregnating the bamboo material with the modified solution; 3) Drying the impregnated bamboo material, heat-treating the bamboo material to cause an in-situ polymerization reaction to occur inside the bamboo material, and finally heating the bamboo material to cause an esterification reaction to occur inside the bamboo material, thereby obtaining an anti-loss bamboo material.
[0009] In some examples, the polyacid is selected from at least one of citric acid, itaconic acid, malic acid, succinic acid, tartaric acid, and maleic acid.
[0010] In some examples, the concentration of polyacid-emulsified glycidyl methacrylate in the microemulsion solution is 2 to 10 wt %.
[0011] In some examples, the molar ratio of the carboxyl group of the polyacid to the epoxy group of glycidyl methacrylate is 0.5 to 1.5.
[0012] In some examples, the emulsification temperature is 60-100° C., and the emulsification time is 10-120 min.
[0013] In some examples, the polymerization initiator in step 2) is selected from any one of ammonium persulfate, potassium persulfate, hydrogen peroxide, and azobisisobutylamidine hydrochloride.
[0014] In some examples, the amount of the polymerization initiator added in step 2) is 0.5-5% of the mass of the polyacid-emulsified glycidyl methacrylate in the microemulsion.
[0015] In some examples, the temperature of the in-situ polymerization reaction in step 3) is 60-100° C. and the time is 6-8 h.
[0016] In some examples, the temperature of the esterification reaction in step 3) is 100-160° C., and the time is 1-4 h.
[0017] In a second aspect, the present invention provides mildew-resistant modified bamboo material prepared by the method for mildew-resistant modification of bamboo material described in the first aspect.
[0018] The beneficial effects of the present invention are: When the concentration of glycidyl methacrylate selected by the present invention reaches 4 wt %, the bamboo material can achieve a good mildew-proof effect; when the concentration reaches above 6 wt %, the bamboo material can achieve a complete mildew-proof effect.
[0019] The bamboo material prepared by the present invention has good anti-loss performance, the solute concentration of the modification reagent reaches more than 8 wt %, and the bamboo material can still achieve a complete mildew-proof effect after being immersed in water for 5 days.
[0020] The precursor in the present invention can polymerize in situ to form highly cross-linked polymers after entering the cell cavity of bamboo, so the modified bamboo still retains mildew resistance after water dissolution. In addition, the modified bamboo can effectively maintain the color and texture of the bamboo and does not release irritating gases.
[0021] The bamboo material prepared by the invention has good and stable mildew-proof performance, and the color and texture of the bamboo material do not change significantly before and after the treatment, and no irritating gas is released.
[0022] The invention uses bamboo as a matrix, has low requirements on equipment and processing conditions, is simple to operate, low in cost, and has a good mildew-proof effect. It can effectively solve the problem of mildew during the storage, transportation and use of bamboo, retain the color and texture of the bamboo itself and have no odor, overcome the disadvantage of economic losses caused by the quality reduction of bamboo due to mildew, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The figure shows the changes in infection area of the mildew prevention test between Comparative Example 1 and Examples 1-2.
[0024] Figure 2 The following are comparison photos of Comparative Example 1 and Examples 1-2 before and after the anti-mildew test.
[0025] Figure 3 The figure shows the changes in infection area of the mildew prevention test of Comparative Example 1 and Example 3.
[0026] Figure 4 The following are comparison photos of Comparative Example 1 and Example 3 before and after the mildew prevention test.
[0027] Figure 5 The following are electron microscope photos of the microscopic morphology of Comparative Example 1 (a), Example 2 (b) and Example 3 (c). DETAILED DESCRIPTION
[0028] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0029] The present invention provides a method for improving the anti-mildew property of bamboo materials, the method comprising the following steps: 1) Glycidyl methacrylate and polyacid are uniformly mixed, stirred and heated, and glycidyl methacrylate is emulsified with the polyacid to prepare a microemulsion solution; 2) adding a polymerization initiator to the microemulsion obtained in step 1) to obtain a modified solution, and impregnating bamboo to allow the microemulsion to penetrate into the cell cavity of the bamboo; 3) Dry the impregnated bamboo material, perform heat treatment to cause in-situ polymerization of glycidyl methacrylate, and finally perform heat treatment to cause esterification of glycidyl methacrylate and polyacid to obtain mildew-proof modified bamboo material.
[0030] In step 1), the concentration of polyacid-emulsified glycidyl methacrylate in the microemulsion solution is 2 to 10 wt %; the polyacid is one or more of organic acids containing two or more carboxyl groups, such as citric acid, itaconic acid, malic acid, succinic acid, tartaric acid, and maleic acid, and the molar ratio of the carboxyl group of the polyacid to the epoxy group of glycidyl methacrylate is 0.5 to 1.5; the emulsification temperature is 60 to 100 ° C, and the time is 10 to 120 min.
[0031] Preferably, the solute concentration in the microemulsion solution is 6-10 wt %, the solute is glycidyl methacrylate emulsified with itaconic acid, the molar ratio of carboxyl group to epoxy group is 1:1, the emulsification temperature is 90° C., and the time is 40 min.
[0032] In step 2), the polymerization initiator is any one of ammonium persulfate, potassium persulfate, hydrogen peroxide, and azobisisobutylamidine hydrochloride, and the added amount is 0.5-5% of the mass of the solute, and the solute is glycidyl methacrylate emulsified by a polyacid; the bamboo material is one or more of moso bamboo, early bamboo, light bamboo, green bamboo, and cycad bamboo; the impregnation method is vacuum impregnation, pressurized impregnation, and normal pressure impregnation, with a vacuum degree of -0.1 to -0.08 MPa and an impregnation time of 0.5 to 1.5 h; a pressure of 0.5 to 1.5 MPa and an impregnation time of 2 to 8 h; and a normal pressure impregnation time of 6 to 48 h.
[0033] Preferably, the polymerization initiator is ammonium persulfate, and the added amount is 1% of the solute mass; the bamboo material is moso bamboo, and the vacuum degree is -0.08 MPa for 1 h, the pressure is 0.8 MPa for 3 h, and the normal pressure is for 24 h.
[0034] In step 3), the drying temperature is 25-60°C and the time is 12-48 h; the treatment temperature of the in-situ polymerization reaction is 60-100°C and the time is 6-8 h; the temperature of the esterification reaction is 100-160°C and the time is 1-4 h.
[0035] Preferably, the drying temperature is 25°C and the time is 24 h; the temperature of the in-situ polymerization reaction is 80°C and the time is 8 h; the temperature of the esterification reaction is 140°C and the time is 2 h. Example 1
[0036] S1) Remove the dense layers inside and outside the fresh bamboo and prepare bamboo slices of 50 mm×20 mm×5 mm, dry them until absolutely dry, weigh them, mark them by classification, and seal them for later use; S2) 5.52 g of citric acid was weighed and added to 470 mL of deionized water at room temperature. After dissolving, 24.48 g of glycidyl methacrylate was poured in and heated in a water bath at 90°C for 40 min to obtain a clear and transparent glycidyl methacrylate microemulsion solution with a concentration of 6 wt%; S3) Weighing 0.3 g of ammonium persulfate and dissolving it in a 6 wt% microemulsion solution, immersing the absolutely dry bamboo in the microemulsion solution, and placing it in a vacuum pressure impregnation tank, firstly impregnating it in a vacuum at -0.08 MPa for 1 h, then impregnating it in a pressure at 0.8 MPa for 3 h, and then impregnating it in a normal pressure for 24 h after the pressure is released; S4) After the samples were naturally air-dried, they were placed in an electric forced air drying oven and firstly heat-treated at 80 ℃ for 8 h to make the glycidyl methacrylate undergo in-situ polymerization inside the bamboo, and then heat-treated at 140 ℃ for 2 h to make the glycidyl methacrylate and citric acid undergo further esterification and cross-linking to obtain the mildew-proof bamboo.
[0037] Mildew resistance test: refer to GB / T 18261-2000, place PDA culture medium in the air to fully inoculate airborne bacteria, place two sterilized glass rods with a diameter of 3 mm in the culture dish, and place two samples horizontally on the glass rods. Immediately after inoculation, place the culture dish in an incubator at a temperature of 28℃ and a relative humidity of 85% for 4 weeks, observe the degree of mildew, and evaluate the mildew resistance of bamboo pieces according to GB / T 18261-2000.
[0038] The damage value of the sample obtained in Example 1 was 0 within 4 weeks, indicating that the molar ratio of carboxyl to epoxy in the solution was 0.5 and the concentration of the modifier was 6 wt%, and the modified bamboo material could be completely mildew-proof and had good mildew-proof performance. After 5 days of water immersion, the sample obtained had mildew spots on the 5th day, and the damage value of the sample after 4 weeks was 4, indicating that the lower concentration of the modified solution resulted in a lower degree of polymer cross-linking, and thus the anti-loss performance was insufficient. Example 2
[0039] S1) Remove the dense layers inside and outside the fresh bamboo and prepare bamboo slices of 50 mm×20 mm×5 mm, dry them until absolutely dry, weigh them, mark them by classification, and seal them for later use; S2) 9.2 g of citric acid was weighed and added to 450 mL of deionized water at room temperature. After dissolving, 40.8 g of glycidyl methacrylate was poured in and heated in a water bath at 90°C for 40 min to obtain a clear and transparent glycidyl methacrylate microemulsion solution with a concentration of 10 wt%; S3) Weighing 0.5 g of ammonium persulfate and dissolving it in a 10 wt% microemulsion solution, immersing the absolutely dry bamboo in the microemulsion solution, and placing it in a vacuum pressure impregnation tank, firstly impregnating it in a vacuum at -0.08 MPa for 1 h, then impregnating it in a pressure at 0.8 MPa for 3 h, and then impregnating it in a normal pressure for 24 h after the pressure is released; S4) After the samples were naturally air-dried, they were placed in an electric forced air drying oven and firstly heat-treated at 80 ℃ for 8 h to make the glycidyl methacrylate undergo in-situ polymerization inside the bamboo, and then heat-treated at 140 ℃ for 2 h to make the glycidyl methacrylate and citric acid undergo further esterification and cross-linking to obtain the mildew-proof bamboo.
[0040] The test method for the mildew resistance of bamboo in this embodiment is the same as that in embodiment 1. The damage value of the obtained sample within 4 weeks is 0, indicating that when the molar ratio of carboxyl to epoxy in the solution is 0.5 and the concentration of the modifier is 10 wt%, the modified bamboo can be completely mildew-proof and has good mildew resistance. After 5 days of water immersion, the damage value of the obtained sample within 4 weeks is 0, indicating that the sample has good anti-loss and mildew resistance. Example 3
[0041] S1) Remove the dense layers inside and outside the fresh bamboo and prepare bamboo slices of 50 mm×20 mm×5 mm, dry them until absolutely dry, weigh them, mark them by classification, and seal them for later use; S2) 3.14 g of itaconic acid was weighed and added to 490 mL of deionized water at room temperature. After dissolving, 6.86 g of glycidyl methacrylate was added and heated in a water bath at 90 °C for 40 min to obtain a clear and transparent microemulsion solution with a concentration of 2 wt%; S3) Weighing 0.1 g of ammonium persulfate and dissolving it in a 2 wt% microemulsion solution, immersing the absolutely dry bamboo in the microemulsion solution, and placing it in a vacuum pressure impregnation tank, firstly impregnating it in a vacuum at -0.08 MPa for 1 h, then impregnating it in a pressure at 0.8 MPa for 3 h, and then impregnating it in a normal pressure for 24 h after the pressure is released; S4) After the samples were naturally air-dried, they were placed in an electric forced air drying oven and firstly heat-treated at 80 ℃ for 8 h to make the glycidyl methacrylate undergo in-situ polymerization inside the bamboo, and then heat-treated at 140 ℃ for 2 h to make the glycidyl methacrylate and itaconic acid undergo further esterification and cross-linking to obtain the mildew-resistant bamboo.
[0042] The test method for the mildew resistance of bamboo in this embodiment is the same as that in Example 1. The damage value of the obtained sample within 4 weeks is 4, indicating that the molar ratio of carboxyl group to epoxy group in the solution is 1. When the concentration of the modifier is 2 wt%, the lower concentration of the modified solution cannot make the modified bamboo completely mildew-proof. Example 4
[0043] S1) Remove the dense layers inside and outside the fresh bamboo and prepare bamboo slices of 50 mm×20 mm×5 mm, dry them until absolutely dry, weigh them, mark them by classification, and seal them for later use; S2) 12.56 g of itaconic acid was weighed at room temperature and added to 460 mL of deionized water. After dissolving, 27.44 g of glycidyl methacrylate was poured in and heated in a water bath at 90 °C for 40 min to obtain a clear and transparent microemulsion solution with a concentration of 8 wt%; S3) Weighing 0.4 g of ammonium persulfate and dissolving it in an 8 wt% microemulsion solution, immersing the absolutely dry bamboo in the microemulsion solution, and placing it in a vacuum pressure impregnation tank, firstly impregnating it in a vacuum at -0.08 MPa for 1 h, then impregnating it in a pressure at 0.8 MPa for 3 h, and then impregnating it in a normal pressure for 24 h after the pressure is released; S4) After the samples were naturally air-dried, they were placed in an electric forced air drying oven and firstly heat-treated at 80 ℃ for 8 h to make the glycidyl methacrylate undergo in-situ polymerization inside the bamboo, and then heat-treated at 140 ℃ for 2 h to make the glycidyl methacrylate and itaconic acid undergo further esterification and cross-linking to obtain the mildew-resistant bamboo.
[0044] The test method for the mildew resistance of bamboo in this embodiment is the same as that in embodiment 1. The damage value of the obtained sample within 4 weeks is 0, indicating that when the molar ratio of carboxyl group to epoxy group in the solution is 1 and the concentration of the modifier is 8 wt%, the modified bamboo can be completely mildew-proof and has good mildew resistance. After 5 days of water immersion, the damage value of the obtained sample within 4 weeks is 0, indicating that the sample has good anti-loss and mildew resistance.
[0045] Comparative Example 1 S1) Remove the dense layers inside and outside the fresh bamboo and prepare bamboo slices of 50 mm×20 mm×5 mm, dry them until absolutely dry, weigh them, mark them by classification, and seal them for later use; S2) Soak the absolutely dry bamboo slices in 500 mL of deionized water at room temperature, put them into a vacuum pressure impregnation tank, first impregnate them at -0.08 MPa vacuum for 1 h, then impregnate them at 0.8 MPa pressure for 3 h, and then impregnate them at normal pressure for 24 h after unloading the pressure; S3) After the sample is naturally air-dried, it is placed in an electric blast drying oven and heat treated at 80 °C for 8 h and then at 140 °C for 2 h.
[0046] The test method for the mildew resistance of the bamboo material in this embodiment is the same as that in embodiment 1. The obtained modified bamboo material has mildew spots on the 3rd day, and the damage value of the sample is 4 on the 30th day.
[0047] Comparative Example 2 S1) Remove the dense layers inside and outside the fresh bamboo and prepare bamboo slices of 50 mm×20 mm×5 mm, dry them until absolutely dry, weigh them, mark them by classification, and seal them for later use; S2) 12.56 g of itaconic acid was weighed at room temperature and added to 460 mL of deionized water. After dissolving, 27.44 g of glycidyl methacrylate was poured in and heated in a water bath at 90 °C for 40 min to obtain a clear and transparent microemulsion solution with a concentration of 8 wt%; S3) Weighing 0.4 g of ammonium persulfate and dissolving it in an 8 wt% microemulsion solution, immersing the absolutely dry bamboo in the microemulsion solution, and placing it in a vacuum pressure impregnation tank, firstly impregnating it in a vacuum at -0.08 MPa for 1 h, then impregnating it in a pressure at 0.8 MPa for 3 h, and then impregnating it in a normal pressure for 24 h after the pressure is released; S4) After the samples were naturally air-dried, they were placed in an electric forced air drying oven and firstly heat-treated at 60 ℃ for 8 h to make the glycidyl methacrylate undergo in-situ polymerization inside the bamboo, and then heat-treated at 100 ℃ for 2 h to make the glycidyl methacrylate and itaconic acid undergo further esterification and cross-linking to obtain the mildew-proof bamboo.
[0048] The test method for the mildew resistance of the bamboo material in this embodiment is the same as that in Example 1. The damage value of the obtained sample within 4 weeks is 2, indicating that the molar ratio of the carboxyl group to the epoxy group in the solution is 1, and the concentration of the modifier is 8 wt%. However, when the heat treatment temperature is low, the modified bamboo material cannot be completely mildew-proof, indicating that the heat treatment temperature is too low, resulting in limited crosslinking of the polymer, thereby affecting the mildew resistance of the modified bamboo material.
[0049] Comparative Example 3 S1) Remove the dense layers inside and outside the fresh bamboo and prepare bamboo slices of 50 mm×20 mm×5 mm, dry them until absolutely dry, weigh them, mark them by classification, and seal them for later use; S2) 11.6 g of maleic acid was weighed and added to 450 mL of deionized water at room temperature. After dissolving, 28.4 g of glycidyl methacrylate was poured in and heated in a water bath at 90°C for 40 min to obtain a clear and transparent microemulsion solution with a concentration of 8 wt%; S3) Weighing 0.5 g of ammonium persulfate and dissolving it in an 8 wt% microemulsion solution, immersing the absolutely dry bamboo in the microemulsion solution, and placing it in a vacuum pressure impregnation tank, firstly impregnating it in a vacuum at -0.08 MPa for 1 h, then impregnating it in a pressure at 0.8 MPa for 3 h, and then impregnating it in a normal pressure for 24 h after the pressure is released; S4) After the samples were naturally air-dried, they were placed in an electric blast drying oven and firstly heat-treated at 80 ℃ for 6 h to make the glycidyl methacrylate undergo in-situ polymerization inside the bamboo, and then heat-treated at 140 ℃ for 1 h to make the glycidyl methacrylate and tartaric acid undergo further esterification and cross-linking to obtain the mildew-resistant bamboo.
[0050] The test method for the mildew resistance of the bamboo material in this embodiment is the same as that in Example 1. The damage value of the obtained sample within 4 weeks is 1, indicating that the molar ratio of the carboxyl group to the epoxy group in the solution is 1, and the concentration of the modifier is 8 wt %. When the heat treatment time is shortened, the modified bamboo material cannot be completely mildew-proof, indicating that the heat treatment time is too short, resulting in limited crosslinking of the polymer, thereby affecting the mildew resistance of the modified bamboo material.
[0051] Comparative Example 4 S1) Remove the dense layers inside and outside the fresh bamboo and prepare bamboo slices of 50 mm×20 mm×5 mm, dry them until absolutely dry, weigh them, mark them by classification, and seal them for later use; S2) 22.1 g of tartaric acid was weighed at room temperature and added to 450 mL of deionized water. After dissolving, 27.9 g of glycidyl methacrylate was poured in and heated in a water bath at 90°C for 40 min to obtain a clear and transparent microemulsion solution with a concentration of 10 wt%; S3) Weighing 0.5 g of ammonium persulfate and dissolving it in a 10 wt% microemulsion solution, immersing the absolutely dry bamboo in the microemulsion solution, and placing it in a vacuum pressure impregnation tank, firstly impregnating it in a vacuum at -0.08 MPa for 1 h, then impregnating it in a pressure at 0.8 MPa for 3 h, and then impregnating it in a normal pressure for 24 h after the pressure is released; S4) After the samples were naturally air-dried, they were placed in an electric forced air drying oven and firstly heat-treated at 80 ℃ for 8 h to make the glycidyl methacrylate undergo in-situ polymerization inside the bamboo, and then heat-treated at 140 ℃ for 2 h to make the glycidyl methacrylate and tartaric acid undergo further esterification and cross-linking to obtain the mildew-proof bamboo.
[0052] The test method for the mildew resistance of the bamboo material in this embodiment is the same as that in Example 1. The damage value of the obtained sample within 4 weeks is 2, indicating that the molar ratio of carboxyl groups to epoxy groups in the solution is 1.5. When the concentration of the modifier is 10 wt%, the modified bamboo material cannot be completely mildew-proof, indicating that the molar ratio of carboxyl groups to epoxy groups is too high, which reduces the degree of cross-linking of the polymer, thereby affecting the mildew resistance of the modified bamboo material.
[0053] Comparative Example 5 S1) Remove the dense layers inside and outside the fresh bamboo and prepare bamboo slices of 50 mm×20 mm×5 mm, dry them until absolutely dry, weigh them, mark them by classification, and seal them for later use; S2) 14.68 g of succinic acid was weighed and added to 450 mL of deionized water at room temperature. After dissolving, 35.32 g of glycidyl methacrylate was poured in and heated in a water bath at 90°C for 40 min to obtain a clear and transparent microemulsion solution with a concentration of 10 wt%; S3) Weighing 0.5 g of ammonium persulfate and dissolving it in a 10 wt% microemulsion solution, immersing the absolutely dry bamboo in the microemulsion solution, and placing it in a vacuum pressure impregnation tank, firstly impregnating it in a vacuum at -0.08 MPa for 0.5 h, then impregnating it in a pressure at 0.8 MPa for 2 h, and then impregnating it in a normal pressure for 6 h after the pressure is released; S4) After the samples were naturally air-dried, they were placed in an electric forced air drying oven and firstly heat-treated at 80 ℃ for 8 h to make the glycidyl methacrylate undergo in-situ polymerization inside the bamboo, and then heat-treated at 140 ℃ for 2 h to make the glycidyl methacrylate and succinic acid undergo further esterification and cross-linking to obtain the mildew-resistant bamboo.
[0054] The test method for the mildew resistance of the bamboo material in this embodiment is the same as that in Example 1. The damage value of the obtained sample within 4 weeks is 2, indicating that the molar ratio of the carboxyl group to the epoxy group in the solution is 1, and the concentration of the modifier is 10 wt%. However, when the immersion time is short, the modified bamboo material cannot be completely mildew-proof, indicating that the immersion time is too short, resulting in limited penetration of the microemulsion, thereby affecting the mildew resistance of the modified bamboo material.
[0055] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A method for improving the anti-mildew property of bamboo, characterized in that: The modification method comprises the following steps: 1) Emulsifying glycidyl methacrylate with polyacid to prepare microemulsion; 2) adding a polymerization initiator to the microemulsion obtained in step 1) to obtain a modified solution, and then impregnating the bamboo material with the modified solution; 3) Drying the impregnated bamboo material, heat-treating the bamboo material to cause an in-situ polymerization reaction to occur inside the bamboo material, and finally heating the bamboo material to cause an esterification reaction to occur inside the bamboo material, thereby obtaining an anti-loss bamboo material.
2. The method for mildew-proofing bamboo according to claim 1, characterized in that: The polyacid is selected from at least one of citric acid, itaconic acid, malic acid, succinic acid, tartaric acid and maleic acid.
3. The method for mildew-proofing bamboo according to claim 1, characterized in that: The concentration of polyacid-emulsified glycidyl methacrylate in the microemulsion solution is 2-10 wt %.
4. The method for mildew-proofing bamboo according to claim 1 or 2, characterized in that: The molar ratio of the carboxyl group of the polyacid to the epoxy group of glycidyl methacrylate is 0.5 to 1.
5.
5. The method for mildew-proofing bamboo according to any one of claims 1 to 3, characterized in that: The emulsification temperature is 60-100°C and the emulsification time is 10-120 min.
6. The method for mildew-proofing bamboo according to claim 1, characterized in that: The polymerization initiator in step 2) is selected from any one of ammonium persulfate, potassium persulfate, hydrogen peroxide, and azobisisobutylamidine hydrochloride.
7. The method for mildew-proofing bamboo according to claim 1 or 6, characterized in that: The amount of the polymerization initiator added in step 2) is 0.5-5% of the mass of the polyacid-emulsified glycidyl methacrylate in the microemulsion.
8. The method for improving the mildew resistance of bamboo according to any one of claims 1 to 3, characterized in that: The temperature of the in-situ polymerization reaction in step 3) is 60-100°C and the time is 6-8 hours.
9. The method for improving the mildew resistance of bamboo according to any one of claims 1 to 3, characterized in that: The temperature of the esterification reaction in step 3) is 100-160°C and the time is 1-4 hours.
10. The mildew-resistant modified bamboo material prepared by the method for mildew-resistant modification of bamboo material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Low-temperature oil-heat bamboo modifying processing method
CN107443518A
Long-acting mildew-proof processing method for bamboos
CN109366653A
Cited By
Efficient mildew-proof wood and bamboo material and modification method thereof
CN120307406A